New insights into the evolutionary history of Gnetum (Gnetales). Issue 2 (28th December 2018) - Hou, Chen; Humphreys, Aelys M.; Thureborn, Olle; Rydin, Catarina
Abstract: Gnetum (Gnetales: Gnetaceae) constitutes an evolutionarily isolated gymnosperm clade, comprising about 40 species that inhabit tropical areas of the world. While its closest living relative, the monotypic Welwitschia, has a well–documented fossil record from the Early Cretaceous, Gnetum–like fossils are rare and poorly understood. The phylogeny of Gnetum has been studied previously but the distant relationship to outgroups and the difficulty of obtaining plant material mean it is not yet fully resolved. Most species are tropical lianas with an angiospermous vegetative habit that are difficult to find and identify. Here a new phylogeny is presented based on nuclear and chloroplast data from 58 Gnetum accessions, representing 27 putative species, and outgroup information from other seed plants. The results provide support for South American species being sister to the remaining species. The two African species constitute a monophyletic group, sister to an Asian clade, within which the two arborescent species of the genus are the earliest diverging. Estimated divergence times indicate, in contrast with previous results, that the major lineages of Gnetum diverged in the Late Cretaceous. This result is obtained regardless of tree prior used in the BEAST analyses (Yule or birth–death). Together these findings suggest a correlation between early divergence events in extant Gnetum and the breakup of Gondwana in the Cretaceous. Compared to the old stem ages of major subclades of Gnetum, crown nodes date to the Cenozoic: the Asian crown group dates to the Cretaceous–Paleogene (K–Pg) boundary, the African crown group to the mid–Paleogene, and the South American crown group to the Paleogene–Neogene boundary. Although dispersal must have contributed to the current distribution of Gnetum, e.g., within South America and from Southeast Asian islands to the East Asian mainland, dispersal has apparently not occurred across major oceans, at least not during the Cenozoic.